SPIN EDGE STATES INDUCED BY THE SPIN-ORBIT INTERACTION AND ZEEMAN EFFECT IN RESTRICTED TWO-DIMENSIONAL ELECTRON SYSTEMS - V. L. Grigoryan
We study the spin edge states, induced by the combined effect of Bychkov-Rashba spin-orbit and Zeeman interactions or of Dresselhaus spin-orbit and Zeeman interactions in a two-dimensional electron system, exposed to a perpendicular quantizing magnetic field and restricted by a hard-wall confining potential. An exact analytical formula is derived for the dispersion relations of spin edge states and their energy spectrumis analyzed versus the momentum and the magnetic field. We calculate the average spincomponents and the average transverse position of electron. It is shown that by removing the spin degeneracy, spin-orbit interaction splits the spin edge states not only in the energy but also induces their spatial separation. Depending on the type of spin-orbit coupling and the major quantum number, the Zeeman termin the combination with spin-orbit interaction increases or decreases essentially the splitting of bulk Landau levels while it has a weak influence on the spin edge states.
Keywords: Physics; Electronic structure and electrical properties of surfaces